2012
DOI: 10.1161/hypertensionaha.111.184101
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Decline of Forced Vital Capacity Predicts Future Arterial Hypertension

Abstract: Lung function studies in middle-aged subjects predict cardiovascular disease (CVD) mortality. We studied if greater loss of forced vital capacity (FVC) early in life predicted incident hypertension (HTN). The sample was 3205 black and white men and women in the Coronary Artery Risk Development in Young Adults (CARDIA) study examined between 1985-86 (CARDIA year 0, ages 18-30 years) and 2005-06 and who were not hypertensive by year 10. FVC was assessed at years 0, 2, 5, 10, and 20. Proportional hazard ratios (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 36 publications
3
54
2
Order By: Relevance
“…A decline in the FEV 1 /FVC ratio is associated with decreased left heart chamber size and lower cardiac output, whereas a decline in FVC but with a preserved FEV 1 /FVC ratio is associated with left heart hypertrophy, increased cardiac output, and diastolic dysfunction. These findings are unique because although decline in FVC has previously been associated with incident hypertension (14) and both established COPD and restriction have known associations with cardiovascular disease and poor health outcomes (1-7), how lung and heart structural and functional abnormalities evolve from young adulthood through middle age has not been investigated. We fill this gap in knowledge by reporting that two patterns of lung health loss, that is, decline in FVC (which could be a precursor of developing overt restrictive physiology) and decline in FEV 1 / FVC (a precursor of developing obstructive physiology), are associated with distinct cardiac structural findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decline in the FEV 1 /FVC ratio is associated with decreased left heart chamber size and lower cardiac output, whereas a decline in FVC but with a preserved FEV 1 /FVC ratio is associated with left heart hypertrophy, increased cardiac output, and diastolic dysfunction. These findings are unique because although decline in FVC has previously been associated with incident hypertension (14) and both established COPD and restriction have known associations with cardiovascular disease and poor health outcomes (1-7), how lung and heart structural and functional abnormalities evolve from young adulthood through middle age has not been investigated. We fill this gap in knowledge by reporting that two patterns of lung health loss, that is, decline in FVC (which could be a precursor of developing overt restrictive physiology) and decline in FEV 1 / FVC (a precursor of developing obstructive physiology), are associated with distinct cardiac structural findings.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of adults in the United States documented that both the extent of emphysema and degree of airflow limitation are cross-sectionally associated with reduced left ventricular (LV) filling (13). We previously found an association between decline in FVC and incident hypertension in a population of generally healthy young adults suggesting that losing lung function may present risk of future cardiovascular disease (14).…”
mentioning
confidence: 99%
“…Indeed, large epidemiological studies have clearly shown increased incidence of hypertension (odds ratio, 1.6; 95% confidence interval, 1.3-1.9) in COPD, 8 and links between lung function and hypertension extend beyond obturative disorders. 9 Another very important aspect that may affect cardiovascular risk and vascular function in COPD is the treatment of COPD itself. Several studies have pointed out that COPD treatment, particularly with β2-mimetics and anticholinergic bronchodilators, might increase cardiovascular risk.…”
Section: March 2014mentioning
confidence: 99%
“…Systemic inflammation or traditional cardiovascular risk factors, such as smoking and serum cholesterol, could not fully explain this relationship [4,5]. Recent findings support the hypothesis that a common pathway exists between a decline in lung function and, subsequently, the development of arterial stiffness or hypertension [3,6]. Suggested explanations were shared factors, like infections during childhood or postnatal growth, which could influence both lung function and arterial stiffness.…”
mentioning
confidence: 92%
“…Precursors for cardiovascular diseases, like hypertension and arterial stiffness, are also associated with lower lung function, independent of sex or anthropometrics [2][3][4][5][6]. Currently, there is no explanation for these relationships.…”
mentioning
confidence: 99%